OP29 Peri-natal exposure to parental Crohn's disease is associated with impaired gut barrier, microbiome composition differences and increased risk of Crohn's disease. (30th January 2023) - Lee Dr., S H; Qiu, L; Olivera, P A; Leibovitzh, H; Xue, M; Neustaeter, A; Mbareche, H; Xu, W; Espin-Garcia, O; Aumais, G L; Huynh, H Q; Panaccione, R; et al.
Abstract: Background: Previous studies have shown that offspring of Crohn's disease (CD) patients have a 6-8 fold risk of incident CD than the general population. Also, newborns of women with CD (vs healthy women) have altered stool microbiome composition and elevated fecal calprotectin (FCP). The "peri-natal period" (pregnancy and first year postpartum) is critical for the development and maturation of the gut microbiome as well as immune responses. However, it is unclear if exposure to parental CD diagnosis during the peri-natal period is associated with increased risk of CD. We aimed to investigate whether peri-natal exposure to parental CD (compared to exposure later in life) has an impact on offspring's gut barrier function, microbiome composition, and the offspring's risk of incident CD. Methods: We assessed 1252 healthy offspring (6-35 years of age) of patients with CD who were recruited in the CCC-GEM Project, a large prospective cohort study following healthy FDRs of CD patients. We classified offspring into "peri-natally exposed" or "exposed later in life" to parental CD diagnosis. We measured baseline FCP and urinary fractional excretion ratio of lactulose to mannitol (marker of intestinal permeability, LMR). Fecal microbiome composition was determined by 16S rRNA gene sequencing. General estimating equation regression and Cox-proportional hazard modeling was used to assess if peri-natal exposure to parental CD is associated with LMR, FCP, altered microbial composition, and future CD onset. Offspring's age and sex and family clusters were accounted for in the models. Results: Offspring exposed to a CD parent peri-natally have a 4.73 fold higher risk (aHR 95%CI 1.28-17.46) of developing CD compared to those exposed to a parent who developed CD later in life (11/586 vs 3/666). Baseline LMR was significantly higher in the offspring exposed to parental CD peri-natally (p=0.003) while no significant difference was observed for FCP at recruitment (p=0.94). We identified five bacterial taxa that were significantly increased in the peri-natally exposed group (FDR-adjusted p<0.05). In a subgroup of offspring of mothers with CD, a dose effect between exposure age and risk was seen; the earlier the offspring was exposed to mother's CD diagnosis peri-natally, the higher the offspring's risk of CD development; this trend was not seen in offspring of fathers with CD. Conclusion: Offspring exposed to parental CD peri-natally had a higher risk of developing CD than those exposed to parental CD later in life. Early life exposure to parental CD was associated with higher baseline LMR and altered bacterial taxa. These results suggest that environmental exposure during the critical peri-natal period may determine the offspring's future risk of developing CD.